MASYARAKAT PETANI DI TENGAH ARUS GLOBALISASI (PEASENT COMMUNITY IN THE GLOBATIZATION) - Nugroho, Tri (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2005)
Up to the present time, the life of peasant community enjoys not much changes: burdened with poverty, suffers, dependence and frequently be the victim of social injustice. The globalization current is indicated with profit hunting of the capital owners, meanwhile the neglecting of common welfare made their life worsened. It is not surprising when many of them just accept the bad fate, suffering life and impossibility to change. This article studying the characteristics, challenge and the globalization chance tries to seek alternative answers, those are the possibility to change and innovate their life, and accepting the bad fate is not a must.